Complications After Endoscopic Laryngopharyngeal Surgery. (10th October 2017) - Kishimoto, Yo; Sogami, Tohru; Uozumi, Ryuji; Funakoshi, Makiko; Miyamoto, Shin‐ichi; Kitamura, Morimasa; Suzuki, Chiaki; Muto, Manabu; Tateya, Ichiro; Omori, Koichi
Abstract : Objectives/Hypothesis: Endoscopic laryngopharyngeal surgery (ELPS), a hybrid of head and neck surgery and gastrointestinal endoscopic treatment, has been attracting attention as a new therapeutic modality for superficial laryngopharyngeal cancers. Although this technique is less invasive than traditional open procedures, some complications including postoperative bleeding, subcutaneous emphysema, or aspiration pneumonia can occur after treatment. The purpose of this study was to investigate the complications associated with ELPS to better understand the indications for this procedure. Study Design: Retrospective medical chart review. Methods: One hundred five patients with 159 laryngeal or pharyngeal lesions were treated with ELPS between August 2009 and September 2015 at Kyoto University Hospital. In total, 147 resections were performed, and complications after the resections were reviewed. Results: Of the 147 resections, postoperative bleeding, subcutaneous emphysema, and aspiration pneumonia were observed in 10, 17, and 10 cases, respectively. All cases with postoperative bleeding and aspiration pneumonia occurred in patients over 65 years of age. A history of taking anticoagulation/platelet medications, and macroscopic 0–IIa lesions were shown to correlate with postoperative bleeding after ELPS. Resection of lesions in the pyriform sinus was found to be associated with subcutaneous emphysema. Conclusions: All complications after ELPS were safely managed. A history of taking anticoagulation/platelet medications and macroscopic 0–IIa lesions were identified as risk factors for postoperative bleeding, whereas resection of pyriform sinus lesions was found to be a risk factor for subcutaneous emphysema. These risk factors should be carefully considered when treating pharyngeal and laryngeal lesions by ELPS. Level of Evidence: 4. Laryngoscope, 128:1546–1550, 2018